Ecosystem service assessment under ecological restoration programs: A systematic review of studies from China - Liu, Junyan; Du, Jie; Zhang, Chenfeng; Zhang, Jindong; Yang, Hongbo; Donald, Marion L.; Wu, Yan; Dong, Tingfa (Frontiers in Ecology and Evolution, 2023)
With a growing body of literature on the topic of ecosystem service (ES), there is an urgent need to summarize ES research in the context of ecological restoration programs (ERPs) in China and identify knowledge gaps for future directions. We conducted a systematic literature review of articles to examine the use of ES approaches for ERP assessments. Our results showed that previous studies mainly focused on the Shaanxi Province, and more than half of the reviewed studies considered no more than three ES types simultaneously. All ES categories were not covered equally; most of the studies focused on provisioning and regulating services, while cultural services have received little attention. Although regional-scale and short-term assessments dominated the reviewed papers, we suggest that multiple temporal and spatial scales for ERP assessments should be given more attention in future work. Moreover, we highlight that an oversimplified land use/land cover (LULC) categorization scheme may potentially lead to inaccuracies and biases in ESs detection under restoration programs. Based on this review, our findings can guide future ERP assessments by using the ES approach. Meanwhile, given the global LULC change brought by the proliferation of plantations under ERPs, our results are also expected to provide a path forward to assess ESs associated with LULC change globally.